Contributions of CIALCA to technical and scientific knowledge ecosystem of agriculture-based livelihoods in the Great Lakes Region - Sartas, Murat; Remans, Roseline; Gotor, Elisabetta (2021)
Since 2016, The Consortium for Improving Agriculture-based Livelihoods in Central Africa (CIALCA) has been conducting research, generating information and scientific and practical knowledge about different parts of the agricultural sectors in Burundi, Eastern Democratic Republic of Congo (DRC) and Rwanda and to a lesser extent in Uganda and Tanzania. In addition, due to its continuity and intensive capacity development efforts, the knowledge and the science generated by CIALCA has been spreading for more than a decade and currently being utilized by many researchers working in the Great Lakes Region.